Remmus Othiambo on how CCAFS is supporting his community - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In May 2014 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa met up with a few of the farmers they work with in Kenya to talk about how the collaboration is going, what has happened since last time and if the activities are having an impact on the community and on the farmers. Remmus Othiambo is one of the members in Lower Kamula Village youth group who has received support from CCAFS EA to build a greenhouse and received training on how to manage and keep fish and do drip-irrigation, among many things. The Youth Group has many plans for the future when it comes to expanding and improving their farming activities.